The Influence of User Involvement, Personal Technical Skills, and User Satisfaction on the Performance of Accounting Information Systems at PT Hariff Daya Tunggal Engineering (Hariff DTE) - Nida Agustin; Palupi Permata Rahmi; Wendi Yuliawan (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of user involvement, personal technical skills, and user satisfaction on the performance of the accounting information system (AIS) at PT Hariff Daya Tunggal Engineering (Hariff DTE). The implementation of the SAP ERP system requires adequate human resource readiness to ensure optimal system performance. This research employs an associative method with a survey approach involving 60 respondents who use the SAP ERP system. Data were collected using Likert-scale questionnaires and analyzed through multiple linear regression, supported by validity tests, reliability tests, classical assumption tests, t-tests, F-tests, and the coefficient of determination (R²). The results indicate that user involvement, personal technical skills, and user satisfaction significantly influence AIS performance, both partially and simultaneously. Partially, user involvement contributes 20.03%, personal technical skills 36.52%, and user satisfaction 26.10%. Simultaneously, the three variables significantly affect AIS performance by 82.6%, while the remaining 17.4% is explained by other factors not examined in this study. These findings highlight that the success of accounting information system implementation is not solely determined by technology, but also by active user engagement, adequate technical competence, and user satisfaction with the system.